Vacuum/Compression Valving (VCV) using parrafin-wax on a centrifugal microfluidic CD platform - Al-Faqheri, Wisam; Ibrahim, Fatimah; Thio, Tzer Hwai Gilbert; Moebius, Jacob; Joseph, Karunan; Arof, Hamzah; Madou, Marc (Public Library of Science, 2013)
This paper introduces novel vacuum/compression valves (VCVs) utilizing paraffin wax. A VCV is implemented by sealing the venting channel/hole with wax plugs (for normally-closed valve), or to be sealed by wax (for normally-open valve), and is activated by localized heating on the CD surface. We demonstrate that the VCV provides the advantages of avoiding unnecessary heating of the sample/reagents in the diagnostic process, allowing for vacuum sealing of the CD, and clear separation of the paraffin wax from the sample/reagents in the microfluidic process. As a proof of concept, the microfluidic processes of liquid flow switching and liquid metering is demonstrated with the VCV. Results show that the VCV lowers the required spinning frequency to perform the microfluidic processes with high accuracy and ease of control.